Development and biocompatibility assessment of alginate–ulvan hydrogels for potential medical use - Pai‐An Hwang; Pei-Syuan Huang; Fu-Yin Hsu (Carbohydrate Polymer Technologies and Applications, 2025)
Traumatic brain injury can severely disrupt brain tissue and pose life-threatening risks due to swelling, hematoma formation, and cerebrospinal fluid abnormalities. The standard treatment involves a two-stage surgical approach: decompressive craniectomy followed by cranioplasty. However, the prolonged absence of skull coverage can lead to significant complications. The aim of this study was to develop an alginate–ulvan hydrogel for single-stage cranial repair to mitigate these challenges. The hydrogels were fabricated using ionic crosslinking and characterized for their physical, mechanical, and biological properties. Scanning electron microscopy revealed interconnected porous structures, facilitating the oxygen and nutrient transport essential for tissue engineering. Fourier transform infrared analysis confirmed successful crosslinking between the alginate and ulvan components. Mechanical testing revealed that increasing the alginate content increased the Young's modulus and hardness, whereas the addition of ulvan reduced the mechanical strength. The water retention and shrinkage ratio tests demonstrated that a higher alginate content improved structural stability by decreasing water uptake. Cytotoxicity assays confirmed the hydrogels’ biocompatibility, with NIH3T3 fibroblasts and HOS osteoblast-like cells exhibiting favorable attachment and proliferation. These findings suggest that alginate–ulvan composite hydrogels are promising candidates for single-stage cranial repair that offer both mechanical stability and biocompatibility to effectively address postcraniotomy complications.